High Co-Expression of PDCD1/TIGIT/CD47/KIR3DL2 in Bone Marrow Is Associated with Poor Prognosis for Patients with Myelodysplastic Syndrome. (8th February 2023) - Zhong, Mengjun; Chen, Cunte; Zhao, Wenshu; Tan, Jiaxiong; Chen, Jie; Huang, Xin; Li, Yangqiu; Dai, Min
Abstract : Cellular immune disorder is a common characteristic of myelodysplastic syndrome (MDS). Abnormal natural killer (NK) cell function has been reported in MDS patients, and this is closely related to disease progression and poor prognosis. However, little is known about the association between the abnormal immune checkpoint (IC) that results in abnormal immune NK cell function and the prognosis of MDS. In this study, RNA-sequencing data from 80 patients in the GSE114922 dataset and bone marrow (BM) samples from 46 patients with MDS in our clinical center were used for overall survival (OS) analysis and validation. We found that the NK cell-related IC genes PDCD1, TIGIT, CD47, and KIR3DL2 had higher expression and correlated with poor OS for MDS patients. High expression of PDCD1 or TIGIT was significantly associated with poor OS for MDS patients younger than 60 years of age. Moreover, co-expression of PDCD1 and TIGIT had the greatest contribution to OS prediction. Interestingly, PDCD1, TIGIT, CD47, and KIR3DL2 and risk stratification based on the Revised International Prognostic Scoring System were used to construct a nomogram model, which could visually predict the 1-, 2-, and 3-year survival rates of MDS patients. In summary, high expression of IC receptors in the BM of MDS patients was associated with poor OS. The co-expression patterns of PDCD1, TIGIT, CD47, and KIR3DL2 might provide novel insights into designing combined targeted therapies for MDS.